Makna Gramatikal dan Leksikal pada Lirik Lagu Sialan Karya Andrian Khalif - Saputri, Pramita Yun; Wahyono, Hari (Kajian Bahasa dan Sastra (KABASTRA), 2025)
This research aims to analyze the grammatical and lexical meaning of the lyrics of the song "Damn" by Andrian Khalif. The method used in this research is qualitative descriptive analysis with a semantic approach. The research results show that the lexical meaning in the song lyrics contains elements such as repetition, collocation, hyponymy, synonymy and antonymy. In addition, grammatical meaning includes affixation, reduplication and composition processes that enrich the language structure in song lyrics. The use of grammatical meaning also includes personal references and puns that add depth to the meaning of the lyrics. Meaning itself includes various aspect, namely, words, phrases, sentences, and text. This research provides an important contribution in understanding the complexity of language meaning in song lyrics as a form of artistic expression.